Reconstituting the state: City powers and exposures in Chicago's infrastructure leases. (May 2016) - Ashton, Philip; Doussard, Marc; Weber, Rachel
In the 2000s, cities across North America began leasing existing infrastructure to global investment consortia. Previous evaluations of infrastructure leases focus on the lack of transparency of the privatisation process and the terms of the arrangements negotiated by the public sector and the private concessionaires. In this research, we argue that such approaches fall short by failing to investigate the significant repositioning of the local state relative to financial markets produced by their involvement in major asset lease deals. We develop this argument through a case study of the institutional transformation of the City of Chicago, the US's most aggressive instigator of infrastructure asset leases. Even as the concession agreements seemingly protect the City from the claims of investors, creditors and counterparties and provide it with new powers, they enmesh the City in a set of financial relationships that expose it to liabilities not accounted for in lease agreements and create an institutional bias towards managing the collateral effects of financialisation.